NAGGETO (Tofu Vegetable Nugget) Innovation Contemporary Healthy Food in Setapuk Besar Village, North District Singkawang - Fitriyadi, Slamat; kamaruddin, Kamaruddin; Utama, Erdi Guna; Yanti, Lili; Zulfahita, Zulfahita; Kariadi, Dodik; Triani, Susan Neni; Mayasari, Dian (STKIP Singkawang, 2023)
Based on the results of a survey conducted by the Community Service team (Lecturers and Students of STKIP Singkawang) in early December 2022 in Setapuk Besar sub-district, North Singkawang district, Singkawang city, the community, especially their mothers, often provide practical frozen food, especially nuggets made from processed meat to their children as a provision for school meals and side dishes at home, This is done because they consider this type of food more practical to serve, durable, nutritious and durable when frozen in the refrigerator, this is done continuously until now because of ignorance or lack of insight and knowledge of mothers who do not realize that behind the practicality of the food it turns out to contain various ingredients that are very dangerous when consumed continuously in the long term. On that basis, the service team consisting of STKIP Singkawang lecturers, STKIP Singkawang Counseling Guidance students and PKK mothers in Setapuk Besar Village, North Singkawang District, Singkawang City made innovations in the form of healthier Nuggets with tofu ingredients as protein and mustard greens as a source of dietary fiber and vitamins. The purpose of this activity is to educate and train people to make healthier and more natural nuggets. The method in this service is training / training and providing insight into healthy food choices. In this activity, the service team together with PKK mothers succeeded in making Naggeto (tofu nuggets and mustard greens) which were then used for school children's provisions and marketed in the Setapuk Besar sub-district area, North District Singkawang, Singkawang City. As for some limitations that exist in doing marketing, the service team in the near future will provide marketing assistance using digital platforms (Facebook, Instragam, Tik-tok) to increase sales targets.